ESTABLISHMENT OF A RELIGIOUS CULTURE IN SCHOOL - Ubabuddin Ubabuddin; Umi Nasikhah; Adi Subowo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The moral crisis that occurs today makes an anxiety for all circles, not least schools as an institution that prints a generation of directors are constantly demanded to improve services in order to produce knowledgeable output, and good character. Various events such as brawl, promiscuity, abuse of illegal drugs, immoral acts, sexual harassment always adorn the school. If the abuse is allowed to continue, then all moral depravity will become a bad culture in school. Education is expected to provide a way out and have a role in shaping human beings who are intellectual and Islamic. To realize it all, it is important to make the school atmosphere with religious culture through planting, habituation, cultural imitation based on Islamic shari'ah by all school residents.